The International Society for Engineering Pedagogy: the Achievements for 45 Years - A. N. Solovyev; V. M. Prikhodko (Moscow Polytechnic University, 2018)
The paper highlights the development of the International Society for Engineering Pedagogy (IGIP) during 45 years since its establishment and its entering into the international system of societies for engineering education. The authors also analyze the reports given at recent IGIP conferences on engineering education. These reports focus on the need of changing the content of engineering education in the framework of the "Agenda for sustainable development", as well as teaching methods in the era of "digital technologies". For the last years the IGIP conferences are being held conjointly with the ICL (Interactive Collaborative Learning) conferences. The participants of the conferences emphasize that the teamwork should be viewed as a basis for problem-oriented learning which is used in many technical universities all over the world. The widely implemented CDIO ideology also provides for teamwork. In conclusion the authors show the role of the Russian technical universities in the development of international integration of engineering education.